A community-based approach to address lung cancer screening disparities in the black community using the Witness Project® framework: development and pilot trial - Lisa Carter-Bawa; Jamie S. Ostroff; Deborah O. Erwin; Elan N. Shoulders; Detric Johnson; Mikhalya Brown; Francis Valenzona; Lina Jandorf (BMC Public Health, 2025)
Abstract Background Disparities in lung cancer outcomes persist among Black Americans, necessitating targeted interventions to address screening inequities. This paper reports the development and refinement of Witness Project® Lung, a community-based initiative tailored to the specific needs of the Black community, aiming to improve awareness and engagement with lung cancer screening. Methods Utilizing a user-centered design and guided by the original Witness Project® framework – an evidence-based lay health advisor intervention program originally developed to increase knowledge and awareness about breast cancer risk and screening in the Black community and later trans-created to the cervical and colorectal cancer screening contexts - Witness Project® Lung was developed and refined through qualitative input from key stakeholders in the Black faith community. Guided by the PEN-3 model and the Conceptual Model for Lung Cancer Screening Participation, the program underwent a rigorous development process to ensure cultural relevance and was pilot tested in the New York City metropolitan area in faith-based and community-based organizational sites in the Black community. Results Pilot testing conducted in New York and New Jersey demonstrated high acceptability, satisfaction, and increased knowledge among participants. The community-based approach, culturally sensitive messaging, and partnerships with faith-based organizations were critical to the refinements of Witness Project® to Witness Project® Lung. The program’s focus on addressing social determinants of health and its delivery by trained lay health advisors showcased feasibility and potential effectiveness. Witness Project® Lung presents a promising alternative to traditional health system-based interventions for improving lung screening rates among Black Americans. Conclusions The community-based, culturally tailored approach, coupled with the involvement of trusted community leaders, has the potential to reduce disparities in lung cancer outcomes. Further research is needed to assess the long-term impact and cost-effectiveness of Witness Project® Lung in promoting lung screening uptake and improving health outcomes within underserved populations.